Possible role of intragenic DNA hypermethylation in gene silencing of the tumor suppressor gene NR4A3 in acute myeloid leukemia. (November 2016) - Shimizu, Ryo; Muto, Tomoya; Aoyama, Kazumasa; Choi, Kwangmin; Takeuchi, Masahiro; Koide, Shuhei; Hasegawa, Nagisa; Isshiki, Yusuke; Togasaki, Emi; Kawajiri-Manako, Chika; Nagao, Yuhei; Tsukamoto, Shokichi; et al.
Highlights: The region encompassing exon 3 of NR4A3 is hypermethylated in AML. Decitabine restores the expression of NR4A3 in AML. Decitabine demethylates CpG at the region encompassing exon 3 of NR4A3 in AML. Intragenic DNA hypermethylation is associated with NR4A3 silencing in AML. Abstract: Expression of the tumor suppressor gene NR4A3 is silenced in the blasts of acute myeloid leukemia (AML), irrespective of the karyotype. Although the transcriptional reactivation of NR4A3 is considered to have a broad-spectrum anti-leukemic effect, the therapeutic modalities targeting this gene have been hindered by our minimal understanding of the transcriptional mechanisms regulating its expression, particularly in human AML. Here we show the role of intragenic DNA hypermethylation in reducing the expression of NR4A3 in AML. Bisulfite sequencing analysis revealed that CpG sites at the intragenic region encompassing exon 3 of NR4A3, but not the promoter region, are hypermethylated in AML cell lines and primary AML cells. A DNA methyltransferase inhibitor restored the expression of NR4A3 following a reduction in DNA methylation levels at intragenic CpG sites. The in silico data revealed an enrichment of H3K4me1 and H2A.Z at exon 3 of NR4A3 in human non-malignant cells but that was excluded specifically in leukemia cells with CpG hypermethylation. This suggests that exon 3 represents a functional regulatory element involved in the transcriptional regulation of NR4A3 . Our findings improve the current understanding of the mechanism underlying NR4A3 silencing and facilitate the development of NR4A3 -targeted therapy.